2014
DOI: 10.11113/jt.v68.3028
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and Characterization of Cellulose from Empty Fruit Bunch (EFB) Fiber

Abstract: In recent years, the use of cellulose fibers in many fields has attracted significant scientific attention due to consumer and environmentally benign, especially in plastic industry, which has been used as cost–cutting fillers and hence provides the possibility of reinforcing polymers. Cellulose can be extracted from natural fibers by chemical and mechanical methods. However, the existing procedures either produce low yields and not environment friendly or energy efficient. The objective of this study was to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 18 publications
1
25
0
2
Order By: Relevance
“…All the diffractograms displayed that the typical peaks of semicrystalline materials consist of broad hump amorphous region and sharp intense peak of crystalline region [21,37]. Cellulose diffractogram showed three peaks around 2 = 16 ∘ , 22.5 ∘ , and 34.5 ∘ which are related to the typical type of cellulose I and corresponding to the crystallographic planes that are (101), (002), and (040) [3,27,38]. At NCC diffractogram, the peaks at 2 = 22.5 ∘ are getting sharper and more intense showing that the sample is more crystalline.…”
Section: Fourier Transform Infrared Spectroscopy (Ftir)mentioning
confidence: 95%
See 1 more Smart Citation
“…All the diffractograms displayed that the typical peaks of semicrystalline materials consist of broad hump amorphous region and sharp intense peak of crystalline region [21,37]. Cellulose diffractogram showed three peaks around 2 = 16 ∘ , 22.5 ∘ , and 34.5 ∘ which are related to the typical type of cellulose I and corresponding to the crystallographic planes that are (101), (002), and (040) [3,27,38]. At NCC diffractogram, the peaks at 2 = 22.5 ∘ are getting sharper and more intense showing that the sample is more crystalline.…”
Section: Fourier Transform Infrared Spectroscopy (Ftir)mentioning
confidence: 95%
“…The OPEFB fiber was treated by soxhlet extraction, alkali treatment (4% NaOH solution), and bleaching treatment to remove lignin and hemicellulose until the white cellulose was obtained [21,27,28]. Then, the NCC was isolated by the method adopted from [21] with slight modifications; that is, acid hydrolysis was conducted at 60% of aqueous H 2 SO 4 for 40 minutes at 45 ∘ C under mechanical stirring.…”
Section: Preparation and Modification Of Nanocrystalline Cellulose (Nmentioning
confidence: 99%
“…Sebanyak 25-26% dari total produksi kelapa sawit tersebut merupakan tandan kosong yang menjadi produk samping. Baru sebanyak 10% dari TKKS tersebut yang sudah dimanfaatkan untuk bahan bakar boiler maupun kompos, dan sisanya masih menjadi limbah (1) . Tabel 1 menunjukkan sebaran produksi terbesar kelapa sawit beberapa propinsi di Indonesia.…”
Section: Latar Belakangunclassified
“…767.500 ton = 776.750 ton (1) TKKS yang menjadi limbah = 7.767.500 -776.750 = 6.990.750 ton Potensi selulosa dengan kandungan 37,5% dari TKKS (4) : = 2.621.531 ton Apabila selulosa yang dapat diekstraksi adalah sebesar 80% dari total selulosa dalam TKKS, maka potensi selulosa sebesar 2.097.225 ton. Sehingga, dari hasil perhitungan dapat dilihat bahwa potensi selulosa yang dapat diekstraksi untuk kemudian diolah menjadi bahan baku bioplastik adalah 2.097.225 ton per tahun.…”
Section: …(1)unclassified
“…It is reported that at about 7 million tons per year of EFB was generated. There is a limit utilization of EFB which is only 10% of EFB has been used for boiler and compost fuel, while most of them are discarded or burnt causing serious environmental problem and giving no benefits (Ngadi and Lani, 2014). EFB contains high cellulose about 43%, hemicellulose 24%, and lignin 21% Septevani et al, 2018).…”
Section: Introductionmentioning
confidence: 99%